Biomechanics, energetics and coordination during extreme swimming intensity: effect of performance level - Ribeiro, J.; Figueiredo, P.; Morais, S.; Alves, F.; Toussaint, H.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Sports Sciences, 2017)
The present study aimed to examine how high- and low-speed swimmers organise biomechanical, energetic and coordinative factors throughout extreme intensity swim. Sixteen swimmers (eight high- and eight low-speed) performed, in free condition, 100-m front crawl at maximal intensity and 25, 50 and 75-m bouts (at same pace as the previous 100-m), and 100-m maximal front crawl on the measuring active drag system (MAD-system). A 3D dual-media optoelectronic system was used to assess speed, stroke frequency, stroke length, propelling efficiency and index of coordination (IdC), with power assessed by MAD-system and energy cost by quantifying oxygen consumption plus blood lactate. Both groups presented a similar profile in speed, power output, stroke frequency, stroke length, propelling efficiency and energy cost along the effort, while a distinct coordination profile was observed (F(3, 42) = 3.59, P = 0.04). Speed, power, stroke frequency and propelling efficiency (not significant, only a tendency) were higher in high-speed swimmers, while stroke length and energy cost were similar between groups. Performing at extreme intensity led better level swimmers to achieve superior speed due to higher power and propelling efficiency, with consequent ability to swim at higher stroke frequencies. This imposes specific constraints, resulting in a distinct IdC magnitude and profile between groups.